2011
DOI: 10.1590/s1413-86702011000500003
|View full text |Cite
|
Sign up to set email alerts
|

Length of exposure to the hospital environment is more important than antibiotic exposure in healthcare associated infections by methicillin-resistant Staphylococcus aureus: a comparative study

Abstract: Objectives: Both total antimicrobial use and specific antimicrobials have been implicated as risk factors for healthcare-associated methicillin-resistant Staphylococcus aureus (HCA-MRSA) infection. The aims of this study were: (I) to explore predictors of a new HCA-MRSA infection in comparison with a new healthcare-associated methicillin-sensitive Staphylococcus aureus (HCA-MSSA); (II) to thoroughly assess the role of recent antibiotic use qualitatively and quantitatively. Methods: The time-period for our stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
3
6
0
Order By: Relevance
“…These results agree with those reported in other countries, however, in studies performed with patients treated at the hospital 28,34 . It was observed that oxacillin-resistant S. aureus has an associated resistance to ciprofloxacin (53.1%), sulfamethoxazole-trimethoprim (53.5%) and rifampicin (24.8%) 25 .…”
Section: Discussionsupporting
confidence: 93%
“…These results agree with those reported in other countries, however, in studies performed with patients treated at the hospital 28,34 . It was observed that oxacillin-resistant S. aureus has an associated resistance to ciprofloxacin (53.1%), sulfamethoxazole-trimethoprim (53.5%) and rifampicin (24.8%) 25 .…”
Section: Discussionsupporting
confidence: 93%
“…Our study indicates that prolonged hospital stay is a risk factor for the development of HIs, which is the same result obtained in several prior studies [32,33]. It has been demonstrated that hospital stay itself poses approximately 17.6% risk of hospital infection development, with each night spent in hospital increasing the risk by an additional 0.5% [34].…”
Section: Discussionsupporting
confidence: 90%
“…In the cohort studies, the observed extrinsic RFs were central venous catheter (CVC) placement, 23,25,[50][51][52][53] ICU admission, [54][55][56][57][58] duration of surgery, 13,17,20,24 steroid use, 13,15,59 previous antibiotic use, 55,60 exposure to cephalosporins before the first episode of infection, 58,61 number of administered antibiotics, 53,62 antimicrobial therapy within 90 days, 63 reoperation, 20,64 transfusion, 50,56,64 invasive mechanical ventilation (IMV), 50,52,65 hospitalization time, 66,67 and a high score on the Acute Physiology and Chronic Health Disease Classification System II. 14,55 Other less frequent extrinsic RFs were found ( Supplementary Table S1).…”
Section: Extrinsic Rfs For Infectionmentioning
confidence: 99%